2009
DOI: 10.1348/014466508x397007
|View full text |Cite
|
Sign up to set email alerts
|

Psychological distress amongst immigration detainees: A cross‐sectional questionnaire study

Abstract: Immigration detainees are highly vulnerable to psychological distress. A review of detention policies is recommended in light of this. Immigration detention may have an independent adverse effect on mental health. It is also possible that individuals with mental health problems may be more likely to be detained. Further research is required to investigate this.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
95
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(102 citation statements)
references
References 25 publications
6
95
1
Order By: Relevance
“…A Danish study reported that 45% of 142 newly arrived asylum seekers had been exposed to torture, 26 and a comparable figure (39%) was found in a study of asylum-seekers in the UK. 27 While higher prevalences have been reported, selection bias is an issue in such research: a prevalence of torture of 84% was reported in a study of 134 asylum-seekers in a United States study, but this group had been recruited from a mental health program specifically for survivors of torture and trauma. 28 There are no national data on the prevalence of torture among asylum-seekers in Ireland, but one study reported that 32% of asylum-seekers presenting for mental health care in St. James's Hospital in Dublin over a two-year period had been tortured.…”
Section: Asylum In Irelandmentioning
confidence: 99%
“…A Danish study reported that 45% of 142 newly arrived asylum seekers had been exposed to torture, 26 and a comparable figure (39%) was found in a study of asylum-seekers in the UK. 27 While higher prevalences have been reported, selection bias is an issue in such research: a prevalence of torture of 84% was reported in a study of 134 asylum-seekers in a United States study, but this group had been recruited from a mental health program specifically for survivors of torture and trauma. 28 There are no national data on the prevalence of torture among asylum-seekers in Ireland, but one study reported that 32% of asylum-seekers presenting for mental health care in St. James's Hospital in Dublin over a two-year period had been tortured.…”
Section: Asylum In Irelandmentioning
confidence: 99%
“…Many studies of mental health and migration have been conducted among immigrants from less developed or developing countries in North America (Breslau et al, 2007;Huang, Wong, Ronzio, & Yu, 2007;Takeuchi et al, 2007) and West Europe (Bhugra & Minas, 2007;Huang & Spurgeon, 2006;Leavey, Rozmovits, Ryan & King, 2007;Lindert, Schouler-Ocak, Heinz, & Priebe, 2008;Robjant, Robbins, & Senior, 2009). These studies generally indicate that international migration is a complex process during which external and internal stressors will influence immigrants' mental health resulting in significant adverse clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence indicates that asylum seekers are particularly vulnerable to PTSD due to experiences of pre-migration trauma (Bernardes et al 2010;Crumlish and O'Rourke 2010;Jain 2010;Robjant et al 2009), and having to seek asylum in a county hitherto unknown to them increases their vulnerabilities further. This combined with being HIV-positive and experiencing varied discrimination makes their lives particularly difficult.…”
Section: Resultsmentioning
confidence: 99%
“…For those who are diagnosed with symptoms associated with PTSD, emphasis appears to be more on an individualized medical model of treatment rather than a social model which focuses on their surrounding environment (Bernardes et al 2010;Chantler 2011). Additionally, research suggests that symptoms associated with PTSD are compounded by punitive policies within the United Kingdom (Crumlish and O'Rourke 2010); for instance, lack of adequate social and financial support, lengthy and complicated processes in the application process, stigma associated with asylum seeking status and detention (Bernardes et al 2010;Jain 2010;Robjant et al 2009). …”
Section: Implications For Policy and Practice Ptsd And Its Implicatiomentioning
confidence: 99%